2001
DOI: 10.3354/meps209159
|View full text |Cite
|
Sign up to set email alerts
|

Variable effect of a large suspension-feeding bivalve on infauna: experimenting in a complex system

Abstract: In soft-sediment habitats there are many examples of species that modify their habitat and thus can be expected to have an important influence on macrobenthic community structure. The large, suspension-feeding pinnid bivalve Atrina zelandica adds complexity to soft-sediment habitats by protruding into the water column and altering boundary-flow conditions and by providing predation refuges and substrates for epifaunal settlement. To investigate effects of A. zelandica density on macrobenthic community composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 59 publications
1
21
0
1
Order By: Relevance
“…This, together with the general agreement of results between this survey and Cummings et al (2001), and the provision of a mechanism for A. zelandica to influence macrofauna by Norkko et al (2001), suggests that it is unlikely that the observed relationships between the 2 are due to some unmeasured environmental factor.…”
Section: Species Interactions: Atrina and Benthic Macrofaunamentioning
confidence: 60%
See 1 more Smart Citation
“…This, together with the general agreement of results between this survey and Cummings et al (2001), and the provision of a mechanism for A. zelandica to influence macrofauna by Norkko et al (2001), suggests that it is unlikely that the observed relationships between the 2 are due to some unmeasured environmental factor.…”
Section: Species Interactions: Atrina and Benthic Macrofaunamentioning
confidence: 60%
“…A highly regionalised response of benthic macrofauna to A. zelandica was also observed in the companion A. zelandica-density-manipulation experiment carried out in areas of Mahurangi Harbour and Martins Bay , implying that interactions between A. zelandica and benthic macrofauna were mediated through local species pools. The results found by Cummings et al (2001) and Norkko et al (2001) suggest that inside-harbour relationships are unlikely to be weaker than outside due to increased variability as a result of increased sample size.…”
Section: Species Interactions: Atrina and Benthic Macrofaunamentioning
confidence: 66%
“…Whilst it would be inappropriate to make broad generalisations about the effects of Sabella on hard and soft substrates throughout Port Phillip Bay based on single site/time experiments (e.g. Ruiz et al 1999, Cummings et al 2001) the results of these 2 studies highlight the uncertainty of inferring an invader's impact on the basis of its density and a limited knowledge of its ecology. In terms of prioritising management efforts, quantitative assessment of real impacts is imperative to assess the risk of ecological damage from these species.…”
Section: Discussionmentioning
confidence: 99%
“…m -2 ) rather than low (7.5 ind. m -2 ) densities (Cummings et al 2001). Interestingly, O'Brien et al (2006) examined the effect of Sabella in localised dense patches (clumps of 10 or more ind.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation